Penilaian Dampak Investasi Sosial Program Budidaya Tanaman Hidroponik PT. Pertamina (Persero) Fuel Terminal Tanjung Gerem - Rokhmat Fakhrudin; Yuda Anas Susetyo (Empower : Jurnal Pengembangan Masyarakat Islam, 2021)
Corporate Social Responsibility (CSR) carried out by PT. Pertamina (Persero) Tanjung Gerem BBM Terminal regarding the community empowerment of the Hydroponic Plant Cultivation program through the construction of a Green House in Gerem Village, Grogol District, Cilegon City after an assessment of the impact of social investment using Social Return On Investment (SROI) has had quite good results. Based on the calculation results obtained SROI ratio of 1,160 which means each investment of Rp. 1,- get an impact or benefit of Rp. 1.16. If viewed from the socio-economic side, it can be said that it is feasible to continue, although there must be improvements in several activities such as business groups